Energetic and Economic Analysis of a Micro Gas Turbine Cogeneration System in Residential Buildings in a Tropical Region - F., Basrawi; Yamada, Takanobu (2012)
The study clearifies the energetic and economic performances of a micro gas turbine cogeneration system (MGT-CGS) in residential buildings located in a tropical climate. Three different cases of MGT-CGS were investigated. The first case investigated an MGT with an exhaust heat exchanger (EHE), whereas the second case investigated an MGT with an EHE and absorption heat exchanger (AHE). The third case was similar to the second case but with the addition of inlet air pre-cooling equipment. It was found that Case 2 and Case 3 can utilize more exhaust heat from the MGT and had Energy recovered utilized efficiency ƞER,utilized in the range of 0.36-0.38 during day time. While during night time the ƞER,utilized was in the range 0.70-0.73. The MGT-CGS in Case 3 had higher Fuel energy saving index FESI while compared to a gas turbine with an air conditioner but a lower FESI in comparison to a combined cycle gas turbine. The shortest payback period for this case was 10 years.